2003
DOI: 10.1097/01.tp.0000054835.58014.c2
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of kidney allograft rejection using anti-CD40 and anti-CD86 in primates

Abstract: Both treatment protocols prevented rejection for the duration of the treatment in most animals. Blocking costimulation by anti-CD40 or by anti-CD40 plus anti-CD86 may be an effective method to prevent graft rejection and may obviate the need for other immunosuppressive drugs, especially in the immediate posttransplantation period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
109
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 29 publications
2
109
0
Order By: Relevance
“…The striking inability of PG102-mediated CD40 engagement to trigger early signaling pathways in immune cells is consistent with its reported inhibition of CD40-mediated B cell effector functions (10,11). This also correlates with PG102-mediated inhibition of in vivo CD40-dependent promotion of inflammation and transplant rejection in animal models (12)(13)(14) and early clinical human studies (15). In some regards, this PG102-induced altered CD40 signaling resembles the "alternative" signaling pathways that bacterial superantigens are reported to trigger when they bind TCR/MHC complexes (reviewed in Ref.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The striking inability of PG102-mediated CD40 engagement to trigger early signaling pathways in immune cells is consistent with its reported inhibition of CD40-mediated B cell effector functions (10,11). This also correlates with PG102-mediated inhibition of in vivo CD40-dependent promotion of inflammation and transplant rejection in animal models (12)(13)(14) and early clinical human studies (15). In some regards, this PG102-induced altered CD40 signaling resembles the "alternative" signaling pathways that bacterial superantigens are reported to trigger when they bind TCR/MHC complexes (reviewed in Ref.…”
Section: Discussionsupporting
confidence: 80%
“…Subsequently, a chimeric form of 5D12 (ch5D12) containing human IgG4 constant regions was produced. The ch5D12 mAb prevents development of experimental autoimmune encephalomyelitis in marmosets (12), as well as prolongs the survival of kidney allografts and allows repeated systemic administration of adenoviral gene therapy vectors in rhesus monkeys (13,14). In an open-label dose-escalation phase I/IIa study of Crohn's disease patients, ch5D12 was well tolerated and showed promising clinical benefit (15).…”
mentioning
confidence: 99%
“…Also, the establishment of chimerism in CD154-deficient recipients was shown to require blockade of the CD80/CD86-CD28 pathway (32). Likewise, blockade of both interactions was necessary to prevent acute rejection of solid allografts (18). The rationale for combining CTLA-4Ig and MR1 has previously been reviewed (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental blocking of the CD40-CD154 or the CD80/ CD86-CD28 costimulatory interactions has been shown to prolong allograft survival in rodent models (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). However, in nonhuman primate studies, blockade of a single pathway is not enough to induce tolerance and only prevents the acute rejection of solid allografts as long as the blockade is maintained (18). Likewise, in human MLR, blockade of both costimulatory interactions is essential for the induction of nonresponsiveness (19).…”
mentioning
confidence: 99%
“…However, the efficacy of this MAb in combination with anti-human CD40 has been shown recently in a rhesus monkey kidney transplantation study. 27 The present study demonstrates the functional in vivo activity of ch5D12 and chFun-1 MAbs in a rhesus monkey model of systemic transduction with an Ad vector, for preventing the immune response against the gene therapy vehicle. These results are encouraging as they confirm that it is feasible to block the humoral response induced by systemic injection of an Ad vector, allowing readministration of the vector.…”
Section: Introductionmentioning
confidence: 99%